Degradation in lithium ion battery current collectors. (15th July 2021) - Guo, Liya; Thornton, Daisy B; Koronfel, Mohamed A; Stephens, Ifan E L; Ryan, Mary P
Abstract: Lithium ion battery (LIB) technology is the state-of-the-art rechargeable energy storage technology for electric vehicles, stationary energy storage and personal electronics. However, a wide variety of degradation effects still contribute to performance limitations. The metallic copper and aluminium current collectors in an LIB can be subject to dissolution or other reactions with the electrolytes. Corrosion of these metal foils is significantly detrimental to the overall performance of an LIB, however the mechanisms of this degradation are poorly understood. This review summarises the key effects contributing to metal current collector degradation in LIBs as well as introduces relevant corrosion and LIB principles. By developing the understanding of these complex chemistries, LIB degradation can be mitigated, enabling safer operation and longer lifetimes.